If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3u = -34 + -2u Solving 3u = -34 + -2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '2u' to each side of the equation. 3u + 2u = -34 + -2u + 2u Combine like terms: 3u + 2u = 5u 5u = -34 + -2u + 2u Combine like terms: -2u + 2u = 0 5u = -34 + 0 5u = -34 Divide each side by '5'. u = -6.8 Simplifying u = -6.8
| b^2+6b(0.5)=36 | | 30(2/15) | | 30•2/15 | | 24=6b-4 | | 13=6(x-7)+8 | | 6x+7=2x-37 | | 7b+4a-3a-5b= | | 1.1666x=140 | | 37=5+8x | | 3512/4= | | 11x+3=2x-5 | | X*(2X+5)=25 | | x^3+8x^2-3x-2266=0 | | 4x=3512 | | 1=5(3)+b | | 13x-3y=34 | | 5x^2=2.2x^2+5.88x+3.168 | | 64*3.14= | | 8/6=5/9 | | 3=-1x+1y | | p(5)=1.8 | | n/32=512 | | a^17/4a^9 | | 360=x(x+2) | | 65=2+7x | | 40-2.5x=3 | | 3(p+7)=2(p-3)+p+27 | | h(5)=175(1.028)5 | | 0.4(x-0.45)=9.2 | | 5+8=43 | | Z/5w=8 | | 9=(20/6x) |